The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/ece3.6715
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of soil microbes associated with a grazing‐tolerant grass species, Stipa breviflora, in the Inner Mongolian desert steppe

Abstract: The soil microbial community plays an important role in grassland ecosystem dynamics and has a crucial influence upon plant ecophysiological traits (Andres et al., 2017; Ford, Rousk, Garbutt, Jones, & Jones, 2013). A major challenge in applied ecology is to understand response mechanisms of those complex microbial communities to grazing, especially for those associated with grass species tolerant of grazing. Many studies have demonstrated that herbivores largely determine aboveground biomass, and also directly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 49 publications
0
13
2
Order By: Relevance
“…However, HIS increased nitrogen consumption, which was the same as in HIM and HII. Although the nutrient consumption of HIS did not cause significant between-group differences in our study, the relationship between soil nitrogen content and bacterial communities involved in nitrogen cycling indicated that HIS exhibited oligotrophic status and increased nitrogen consumption [14,[48][49][50][51][52]. The reason may be that forage grass enhances nitrogen cycling and causes nitrogen loss via nitrite reduction [69].…”
Section: The Risks and Benefits Of Planting Forage Grass On Lacontrasting
confidence: 55%
See 1 more Smart Citation
“…However, HIS increased nitrogen consumption, which was the same as in HIM and HII. Although the nutrient consumption of HIS did not cause significant between-group differences in our study, the relationship between soil nitrogen content and bacterial communities involved in nitrogen cycling indicated that HIS exhibited oligotrophic status and increased nitrogen consumption [14,[48][49][50][51][52]. The reason may be that forage grass enhances nitrogen cycling and causes nitrogen loss via nitrite reduction [69].…”
Section: The Risks and Benefits Of Planting Forage Grass On Lacontrasting
confidence: 55%
“…In 2016 and 2017, HIS had significant effects on some oligotrophic bacteria, including Acidobacteria Gp3, Gemm-4, NB1-I, Polaromonas, and Novosphingobium (LDA score > 2, K-W test P < 0.05) [14,[48][49][50]. In 2018, some bacteria involved in nitrogen cycling and plantgrowth promotion increased in the HIS, including Solibacteres, Planctomycetia, Sva0725, Rubrivivax, and Nitrospira (LDA score > 2, K-W test P < 0.05) [51][52][53].…”
Section: The Effects Of Management Scenarios On Microbial Communitiesmentioning
confidence: 99%
“…Among the identified keystone species in our study, the taxa of Udeniomyces , Podospora , Lasiobolidium , Dioszegia , Dothiora , Thyrostroma and Sporormiella were first reported in the desert ecosystem and exhibited specificity to our host plants. In addition, Alternaria was general isolated as the most dominant fungal genera in desert plants as well as other symptomless halophytes [ 9 , 26 , 114 , 115 ]. Although Alternaria is known as a phytopathogen of several plant species, this species was frequently reported as a dominant member of desert ecosystems and displayed a greater adaptive potential [ 71 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…This result may be attributed to the reduction of litter mass, due to the decrease of vegetation coverage and plant biomass caused by livestock grazing [48]. In contrast, the impacts of grazing on TN and TP from different studies were more variable: positive [49], negative [50], and neutral [51] effects were equally common and varied considerably with grassland ecosystem, grazing intensity, and plant diversity. NH 4 + -N and NO 3 − -N are the two main inorganic N sources from soil that can be taken up and utilized by most plants.…”
Section: Grazing-induced Changes In Soil Properties and Plant Characteristicsmentioning
confidence: 99%